Predictive value of vertebral artery extracranial color‐coded duplex sonography for ischemic stroke‐related vertigo. Issue 12 (30th August 2013) - Liou, Li‐Min; Lin, Hsiu‐Fen; Huang, I‐Fang; Chang, Yang‐Pei; Lin, Ruey‐Tay; Lai, Chiou‐Lian
Abstract: Vertigo can be a major presentation of posterior circulation stroke and can be easily misdiagnosed because of its complicated presentation. We thus prospectively assessed the predictive value of vertebral artery extracranial color‐coded duplex sonography (ECCS) for the prediction of ischemic stroke‐related vertigo. The inclusion criteria were: (1) a sensation of whirling (vertigo); (2) intractable vertigo for more than 1 hour despite appropriate treatment; and (3) those who could complete cranial magnetic resonance imaging (MRI) and vertebral artery (V2 segment) ECCS studies. Eventually, 76 consecutive participants with vertigo were enrolled from Kaohsiung Municipal Hsiao‐Kang Hospital, Kaohsiung, Taiwan between August 2010 and August 2011. Demographic data, neurological symptoms, neurologic examinations, and V2 ECCS were assessed. We chose the parameters of peak systolic velocity (PSV), end diastolic velocity (EDV), PSV/EDV, mean velocity (MV), resistance index (RI), and pulsatility index (PI) to represent the hemodynamics. Values from both sides of V2 segments were averaged. We then calculated the average RI (aRI), average PI (aPI), average PSV (aPSV)/EDV, and average (aMV). Axial and coronal diffusion‐weighted MRI findings determined the existence of acute ischemic stroke. We grouped and analyzed participants in two ways (way I and way II analyses) based on the diffusion‐weighted MRI findings (to determine whether there was acute stroke) and neurological examinations. Using way I analysis, the "MRI (+)" group had significantly higher impedance (aRI, aPI, and aPSV/EDV ratio) and lower velocity (aPSV, aEDV, and aMV(PSV + EDV/2)), compared to the "MRI (–)" group. The cutoff value/sensitivity/specificity of aPSV, aEDV, aMV, aPI, aRI, and aPSV/EDV between the MRI (+) and MRI (–) groups were 41.15/61.5/66.0 ( p = 0.0101), 14.55/69.2/72.0 ( p = 0.0003), 29.10/92.1/38.0 ( p = 0.0013), 1.07/76.9/64.0 ( p = 0.0066), 0.62/76.9/64.0 ( p = 0.0076), and 2.69/80.8/66.0 ( p = 0.0068), respectively. Using way II analysis, lower aEDV and aMV, and higher aRI, aPI, and aPSV/EDV ratio could determine the "MRI (+) without focal signs" group. The cutoff value/sensitivity/specificity of aEDV, aMV, aPI, aRI, and aPSV/EDV between the MRI (+) without focal signs and MRI (–) groups were 9.10/71.4/96.0 ( p = 0.0005), 15.65/57.1/96.0 ( p = 0.0124), 1.10/100/70.0 ( p = 0.0002), 0.64/100/70.0 ( p = 0.0023), and 2.80/100/70.0 ( p = 0.0017), respectively. In conclusion, using demographic data and clinical symptoms, it was difficult to determine the patients with ischemic stroke‐related vertigo. Although neurological examinations still have diagnostic value, the high impedance and low velocity pattern of V2 ECCS can be an add‐on method for the screening of acute ischemic stroke‐related vertigo, even for those without focal neurological signs.